A method for measuring the three-dimensional orientation of cortical canals with implications for comparative analysis of bone microstructure in vertebrates. (January 2017) - Pratt, Isaac Vorster; Cooper, David Michael Lane
Highlights: The orientation of cortical canals is believed to be related to bone growth and functional loading. We present here a new method for measuring the orientation of cortical canals. We show the application of this method in a mammal and a bird. This method can be used to study bones from any vertebrate, including mammals, reptiles, and birds. Abstract: The orientation of vascular canals in cortical bone can reveal information about the growth rate and loading environment of a bone. For example, in birds it has been proposed that a high proportion of circumferential canals (a laminar cortex) is related to fast growth or torsional loading related to active flight. In this paper we present a method to measure the three dimensional (3D) orientation of vascular canals. Image data are obtained from micro-CT and two angles are measured: phi, determining how longitudinal a canal is; and theta, determining whether a canal is radial or circumferential. This method can measure the orientation of each canal contained in the scanned images. Here we demonstrate the approach on two samples − a rat tibia and a hawk humerus. This method offers a direct (3D) method for quantifying features of canal orientation, such as the degree of laminarity, and can be applied easily and non-destructively to multiple species and bones. The growth and development of the cortical canal network and its impact on factors such as bone strength and bone quality remains relatively unexplored. Our method provides a new tool to examine the impact of the orientation of cortical bone canals on bone and explore the origins of cortical canals formed during modelling and remodeling. This method has applications in comparative bone biology, small animal models, and human bone studies.